Feed efficiency in swine - Patience, John F. (Wageningen Academic Publishers, 2012)
'Feed efficiency in swine' has been prepared as a comprehensive treatise on the current state of our understanding of this topic which is so important to the pork industry. Each chapter is written by international authorities who understand both the science and application of their topic area. The book provides detailed insight into the many factors affecting feed efficiency, ranging from diet processing to herd health, from nutrition to physiology and from day-to-day barn management to the adoption of advanced technologies. The authors explain such practical aspects as the challenge of interpreting feed efficiency information obtained on farm or the role of liquid feeding. The authors also delve into more scientific topics such as amino acid or energy metabolism or animal physiology. This book is written for people who have a technical interest in pork production, including nutritionists, geneticists, farm management specialists, veterinarians, other academics and, of course, pork producers.